Verses Prohibiting the Violation of Human Rights in the Holy Quran (Property as a Model) (Islamic Sciences Journal, 2026)
This research focuses on the prohibition of unjustly consuming people's wealth. It employs a thematic interpretive approach, which involves linguistically analyzing words, deriving their meanings, and clarifying the intended message of the Quranic verses. The aim is to understand the principles upon which the Quran bases its prohibition of encroaching upon others' wealth, and to demonstrate Islam's concern for its protection and preservation. The research includes defining the main concepts of the topic and conducting an interpretive study of the relevant Quranic verses. The study aims to elucidate the Quranic approach to prohibiting the unjust consumption of people's wealth, to arrive at its ethical and legislative objectives, and to highlight moderation. Legislation in Islam, with an explanation of the fundamental differences between the Islamic vision of human rights as a divine approach, and the Western vision, which consists of man-made laws.
Keywords: The Holy Quran, Rights, Human Being, Property, Theft